Recommendations for writing the material and methods section in scientific studies (Revista Argentina de Cirugía, 2026)
In observational studies, researchers assess the outcomes of a given event without intervening on the defined variables. Observational studies play a fundamental role in medical research by providing relevant information in situations where clinical trials are not feasible or ethically appropriate.